Effect Ownership, Accountant Public Office, and Financial Distress to the Public Company Financial Fraudulent Reporting in Indonesia - Mardiana, Ana (Journal of Economics and Behavioral Studies, 2015)
This study empirically examine the influence of ownership, accountant public office and the financial distress on fraudulent financial reporting. The variables studied were foreign ownership, family ownership, accountant public office and the financial distress of public companies in Indonesia in 2009 to 2012. The research was conducted by quantitative methods using secondary data. Secondary data comes from a list of cases Bapepam-LK and the annual reports listed companies on the Stock Exchange. This population of study was company listed on the Stock Exchange, and then the samples were taken by purposive sampling criteria the company’s corporate criteria sanctioned Bapepam-LK and the sanctions contained elements of fraud, including the non-financial corporate sector and have the data required in this study. At the end, the total sample of 64 companies that the company. This study uses logistic regression statistical tools as the dependent variable is a dummy variable (non-metric), while the independent variable is a variable mixture of metric and non-metric. The results show that the family ownership significantly affect financial reporting fraud but in the opposite direction because of the negative impact. Foreign ownership of a significant negative effect on fraudulent financial reporting. This indicates the greater ownership by the family, the lower the level of financial of fraudulent reporting accountant public office has no effect on fraudulent financial reporting. This occurs because both KAP Big Four and Small Firm have the same standards in Generally Accepted Accounting Principles (GAAP) in carrying out their duties as auditor. Financial distress negatively affects fraudulent financial reporting.